A STUDY OF GREEN PROCUREMENT POLICIES AND STATE CORPORATION PERFORMANCE IN RWANDA - Njoroge, Grace Muthoni; Chebet, Peter Kipchirchir (International Journal of Allied Research in Economics (IJARE), 2023)
In today’s competitive business landscape, enterprises are confronted with mounting pressure from both regulatory bodies and the community to harmonize their economic performance with environmental concerns. The imperative to mitigate the adverse environmental impacts of their products and services has compelled companies to adopt strategies geared towards environmental sustainability. However, the motivation behind this shift is not solely ecological; it is fundamentally rooted in enhancing profitability and fostering robust business practices. Green procurement, the cornerstone of this transformation, ensures that businesses can simultaneously harness economic, environmental, and societal benefits. Historically, green procurement practices were confined to a select few companies, primarily those dealing with chemicals or consumer goods directly influenced by consumer demands. Nevertheless, the past decade has witnessed a surge in awareness regarding environmental issues such as global warming, carbon emissions, hazardous substances, and resource scarcity. This heightened awareness, coupled with activist advocacy and policy initiatives, has spurred a positive response from companies worldwide, driving the widespread adoption of green practices. The motivations for embracing green procurement are twofold, with both internal and external factors at play. Internally, companies are driven by efficiency-related benefits, which encompass improved performance, heightened profitability, and increased productivity. Externally, these companies contend with social pressure from various communities and interest groups, compelling them to incorporate green practices into their operations.